Spatial distribution, multivariate statistical analysis, and health risk assessment of some parameters controlling drinking water quality at selected primary schools located in the southwestern coastal region of Bangladesh. (2nd January 2022) - Kormoker, Tapos; Idris, Abubakr M.; Khan, Mohammed Mahmud; Tusher, Tanmoy Roy; Proshad, Ram; Islam, Md. Saiful; Khadka, Sujan; Rahman, Shaira; Kabir, Md. Humayun; Kundu, Satyajit
Abstract: The southwestern coastal areas of Bangladesh have been severely suffering from the scarcity of safe drinking water due to the combined consequences of hydrogeological processes, groundwater depletion, saltwater intrusion, and adverse anthropogenic activities. This concern results in serious public health hazards, particularly for children at primary schools. This study was conducted to evaluate some physiochemical and bacteriological parameters of drinking water from tube wells (TWs) located at primary schools in Kalapara upazila, Patuakhali district, Bangladesh. Water samples were collected from 65 TWs. The levels of the examined parameters recorded the following ranges: pH 6.9–8.3, electrical conductivity 774.3–1987.0 μS/cm, Fe 0.12–15.78 mg/L, As 0.0–0.03 mg/L, and Cl − 9.0–354.0 mg/L. The results revealed that 11% of TWs exceeded the level of Fe recommended by the National Drinking Water Quality Standard in Bangladesh, while other physiochemical parameters fit with the national standards. The bacteriological analysis revealed that 60% of TWs delivered fecal coliform (FC)-free water, while 40% of TWs supplied total coliform (TC)-free water. However, about 26% of TWs had the potential to pose non-carcinogenic health problems for children from As, while only 5% of TWs were found to cause probable non-carcinogenic risks for adults. The calculated carcinogenic risks values for adult male and female were within the USEPA acceptable range (1 × 10 −4 –1 × 10 −6 ), except for only one sampling point, while four sampling points (6.15% of TWs) exhibited carcinogenic risks for children. This result indicates that the ingestion of drinking water from those TWs may pose lifetime cancer risks to children.